Features of dedemocratization in culture politics of Mexican society - Mendieta Ramírez, Angélica; Estrada Rodríguez, José Luis (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This research work takes several surveys applied at the international and national level, to identify the political culture of citizens on the major issues of the national agenda and their perception of democracy. It warns about the problems that Mexico has around the institutions that guarantee democracy and warns about the features of democratization that opinion polls such as ENCUCI, applied in 2020, can show. At the end, he describes the suggestions based on the theoretical and documentary review of the Mexican case.